Assessment of the tableting characteristics of a novel sorbitol and calcium diphosphate composites (2015)
ABSTRACT: Objective: To improve the tableting properties of sorbitol (SOR) via particle engineering through agglomeration with anhydrous calcium diphosphate (ACD) employing a house-made agglomerator. Methods: A novel SOR: ACD composites were produced by agglomeration at the 95:5; 80:20, 50:50, 20:80 and 6:94 SOR to ACD. The resulting tableting properties such as densification, compressibility, compactibility, ejection force, elastic recovery, sensitivity to lubricants, compression speed and disintegration time were then evaluated. Results: The new agglomerated excipient had better flow, compressibility and compactibility than the physical mixture of SOR and ACD being the 95:5 SOR: ACD ratio the composite that exhibited the best tableting properties. Conclusion: This novel excipient has a potential use as a pharmaceutical aid for direct compression applications.